IMPLEMENTASI PERAN ORANG TUA TERHADAP KEMAMPUAN KEMANDIRIAN BELAJAR SISWA PADA MASA PANDEMI COVID-19 DI MI MANSYAUL HUDA DESA SENDANGREJO KECAMATAN TAYU KABUPATEN PATI - Srifariyati (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2024)
In 2020 around the world there has been an outbreak of a virus, namely Corona Virus Disease (Covid-19). Teaching and learning activities in schools are disrupted, learning which was initially carried out face-to-face for a while cannot be carried out. To overcome these problems, during the Covid-19 pandemic, every school carried out educational activities with distance learning. In this case, the level of parental cooperation with online programs is very important. Because while online, children spend a lot of time at home. Basically human education starts from the family, the family is the first and foremost place for the formation and education of children. This research is a qualitative research with primary data sources are grade 1 to grade 3 students, parents and teachers of MI Mansyaul Huda Sendangrejo Village Tayu Pati. Data collection techniques by observation, interviews and documentation. This research was conducted from January to September 2021. The results of this study are 1) The process of implementing learning at MI Mansyaul Huda, Sendangrejo Village, Tayu District, Pati Regency is carried out in a combination of online and face-to-face according to regional conditions. During the online learning process, the media used was Whatsapp guided by a subject teacher from home. 2) Efforts taken by parents in independent learning of students at MI Mansyaul Huda, Sendangrejo Village, Tayu District, Pati Regency, namely by giving motivation and praise to children, setting good examples, accompanying children when studying, trying to be friends for children, and coaching with the method of advice and educate through habituation and training. 3) Obstacles faced by parents in shaping the independence of MI Mansyaul Huda students, Sendangrejo Village, Tayu District, Pati Regency, namely environmental influences and the influence of mass media, parental education origin, lazy children, and parents who spoil their children too much.